PERANAN EKOLOGI MAKROALGA BAGI EKOSISTEM LAUT - Tri Handayani (Pusat Penelitian Oseanografi LIPI, 2019)
ECOLOGICAL ROLE OF MACROALGAE FOR MARINE ECOSYSTEM. Macroalgae is an ecologically and economically important component in marine ecosystem. Ecologically, macroalgae has a role as a primary producer, food for other marine biota, provide shelter, nursery ground and carbon sink. Macroalgae contains photosynthetic pigments to be able to provide their own food and produce carbon dioxide for other marine biota (called primary productivity). Macroalgae is a food source, provide shelter and nursery ground for fish, gastropods (mollusks), crustaceans and sea urchins. Macroalgae also has the ability to to reduce the effects of global warming through carbon sink. Absorption of carbon emissions of anthropogenic activity by marine organisms are called as blue carbon. Therefore, macroalgae is ecologically importantfor the balancing of marine ecosystems sustainability.